Postpartum subcapsular liver hematoma: a rare complication successfully managed with conservative treatment - Borges, Ana Catarina; Almendra, Rita; Nogueira-Silva, Cristina; Correia, Cátia (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Subcapsular liver hematoma is a spontaneous bleeding between the Glisson’s capsule and the liver parenchyma. It is a rare but serious complication of severe preeclampsia and/or HELLP (hemolysis, elevated liver enzyme and low platelets) syndrome that can have devastating consequences, the worst being hepatic rupture with maternal death. A young nulliparous woman, at 34 weeks ‘gestation, was admitted for evaluation of new onset hypertension. The pregnancy was uneventful, yet at 32 weeks’ gestation a severe fetal growth restriction was diagnosed. She presented a high urine protein to creatinine ratio, then a pre-eclampsia without severity criteria was diagnosed. At day 3 of hospitalization, she presented with intense epigastric pain and vaginal blood loss, so an emergency c-section was performed with the suspicion of placental abruption. Eighteen hours postpartum she complained of intense diffuse abdominal pain radiating to the right shoulder blade. Arterial hypotension and obtundation was observed. A computerized tomography was performed and revealed the presence of a bulky perihepatic hematoma measuring 12×9×21 cm. The patient went into hemorrhagic shock and so massive hemorrhage protocol was activated. After a multidisciplinary discussion a conservative management was decided. Clinical and analytical improvement was observed, and she was discharged home on postpartum day-27. The diagnosis of subcapsular liver hematoma is challenging, but it is essential to be done in a timely manner. Thus, a high index of suspicion, a prompt diagnosis and a multidisciplinary approach are the key factors for a successful outcome.